APLIKASI RANCANGAN GREEN PESANTREN DI SEMARANG - Eddy Prianto; Bambang Sujono; Agung Dwiyanto (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
The development of pesantren (islamic boarding school) in Semarang is very significant as consequence of the Central Java Provincial capital development. As the energi and environmental crisis become the national problem, designing pesantren which responsive to both issues is the aim of this paper, by implementing the green building concept. This paper is Community Service report of Architecture Department lecturers realized in 2016 in cooperation with Al-Manar and Yataama Al-Firdousi Foundations in the process of preparing planning document for the dormitory. Technical implementation of this activity, initiated with a field survey and technical guidance of architectural planning, green building study to the preparation of technical documents / architectural drawings that will be used in the construction stage. Six criteria of Green building measurement applied to pesantren design comprises appropriate site development, energi efficiency and energi saving, water conservation, source materials and recycling, indoor health and comfort and environmental condition of building and building management.